Understanding industry - Stefanou, Rosemarie (London ; Boston : Butterworths in association with the Industrial Society, 1994)
Examines the organization of many manufacturing companies and discusses trade unions, changing technology, employee motivation, and other issues concerning industry and society.
Includes index.
Bibliography: p. 129-133.
Keywords: Industries -- Juvenile literature; Industrial management -- Juvenile literature; Industries -- Great Britain -- Juvenile literature; Industries; Industrial management; Industries -- Great Britain